The effects of preferred and non-preferred running strike patterns on tissue vibration properties - Enders, H.; von Tscharner, V.; Nigg, B. M. (Journal of Science and Medicine in Sport, 2014)
Objectives: To characterize soft tissue vibrations during running with a preferred and a non-preferred strike pattern in shoes and barefoot. Design: Cross-sectional study. Methods: Participants ran at 3.5 m s-1 on a treadmill in shoes and barefoot using a rearfoot and a forefoot strike for each footwear condition. The preferred strike patterns for the subjects were a rearfoot strike and a forefoot strike for shod and barefoot running, respectively. Vibrations were recorded with an accelerometer overlying the belly of the medial gastrocnemius. Thirteen non-linearly scaled wavelets were used for the analysis. Damping was calculated as the overall decay of power in the acceleration signal post ground contact. A higher damping coefficient indicates higher damping capacities of the soft tissue. Results: The shod rearfoot strike showed a 93% lower damping coefficient than the shod forefoot strike (p < 0.001). A lower damping coefficient indicates less damping of the vibrations. The barefoot forefoot strike showed a trend toward a lower damping coefficient compared to a barefoot rearfoot strike. Running barefoot with a forefoot strike resulted in a significantly lower damping coefficient than a forefoot strike when wearing shoes (p < 0.001). The shod rearfoot strike showed lower damping compared to a barefoot rearfoot strike (p < 0.001). While rearfoot striking showed lower vibration frequencies in shod and barefoot running, it did not consistently result in lower damping coefficients. Conclusions: This study showed that the use of a preferred movement resulted in lower damping coefficients of running related soft tissue vibrations.